Black Education : a Transformative Research and Action Agenda for the New Century. (Taylor & Francis, 2005)
This volume presents the findings and recommendations of the American Educational Research Association Sponsored Commission on research in Black Education's investigation of the major issues that hinder the education of Black people in the U.S., other di.